The Seventh Crusade, 1244 - 1254 sources and documents - Jackson, Peter 1961- (Crusade texts in translation, 2007)
The crusading movement bequeathed to its future historians a legacy of sources unrivalled in their range and variety. 'Crusade Texts in Translation' presents these sources in detail as well as the motivations and viewpoints, military efforts and spiritual lives, of the participants in the crusades.